2020
DOI: 10.3390/ijerph17020494
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Mental Health: A Contribution to Understanding the Heterogeneity of Research Findings

Abstract: Most studies report positive associations between religiosity and spirituality and aspects of mental health, while a small proportion report mixed or fully negative associations. The aim of this study was to assess the associations of religiosity measured more specifically, with mental health in a secular environment, using a nationally representative sample of Czech adults (n = 1795). We measured religious affiliation, conversion experience, non-religious attitudes and the stability of these attitudes, mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
(48 reference statements)
0
28
0
2
Order By: Relevance
“…A fifth article studied the effect of religiosity on mental health, concluding that attachment and closeness to God seem important for improving mental health, but it is necessary to consider other socioeconomic factors. In addition, this article considered that a unification of the indicators that measure religiosity is necessary since the results vary widely according to the selected indicators [ 13 ]. Other research has demonstrated that the hedonic and utilitarian performances of volunteer tourism significantly and positively contribute to increasing travellers’ mental health, which ultimately enhances their prosocial intentions [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A fifth article studied the effect of religiosity on mental health, concluding that attachment and closeness to God seem important for improving mental health, but it is necessary to consider other socioeconomic factors. In addition, this article considered that a unification of the indicators that measure religiosity is necessary since the results vary widely according to the selected indicators [ 13 ]. Other research has demonstrated that the hedonic and utilitarian performances of volunteer tourism significantly and positively contribute to increasing travellers’ mental health, which ultimately enhances their prosocial intentions [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these adjectives (e.g., critical, distant, loving, just), 15 were taken from the 2005 Baylor Religion Survey (Baylor University, Waco, TX, USA, 2005). Respondents chose from the possible answers "very well" (1); "somewhat well" (2); "not very well" (3); "not at all (4)". The respondents who identified themselves as believers and were further considered as religious described how well in their opinion the adjectives describe God.…”
Section: Methodsmentioning
confidence: 99%
“…However, their responses can still offer a certain image of God, who they do not believe in [44]. For the purpose of statistical analysis, each item was dichotomized following the approach of Malinakova et al [3]. Therefore, only the respondents from both the religious and nonreligious groups who declared a full agreement/disagreement with a specific adjective were considered as seeing God in this way.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations